Structural assessment of a proposed precast wall connection under combined loading - Vaghei, Ramin (2016)
The industrialized building system (IBS) is defined as a construction technique in which the system components are manufactured in a controlled environment on-site or off-site, transported, positioned, and assembled into a structure with minimal additional site work. The connection of precast components in IBS structures is an important factor that play important role in integrity of building and provides stability to buildings subjected to various loads. However, the stability of the building type constructed using IBS is a challenging issue against dynamic loads. And there is a lack of knowledge when the connections of IBS are prepared particularly when those connections subjected to dynamic load caused by earthquakes. Also, based on extensive review of literature, there is no proper analytical and numerical model that can cater for connections and joints of IBS particularly in wall to wall connection. Hence, this study proposes a new connection for precast concrete wall-to-wall joints subjected to static and dynamic loads. The proposed system is designed to resist multidirectional imposed loads and reduces vibration effects.The proposed connection is comprised of male and female steel channels and rubber positioned between of male and female connection to dissipate the vibration energy induced by dynamic load.In order to evaluate performance of proposed connection during imposed load, analytical model for the IBS structure was developed. For this purpose, constitutive law and mathematical model for the IBS members, including: walls and connections are formulated and finite element algorithm is developed. In order to develop finite element formulation for proposed connection is required to determine stiffness of connection in all 6 degree of freedoms (DOFs). For this purpose, six samples of fabricated wall to wall joint equipped by proposed connection are subjected to pushover test in all 6 DOFs, and six more specimens of wall to wall joint equipped by common connection are fabricated besides in order to compare the performance of U-shaped steel channel connection (i.e. proposed connection) and loop connection (i.e. common connection). The stiffness values which determined through experimental test for each DOF are placed in the stiffness matrix derived from analytical model for the connection. The developed analytical model is codified and implemented in finite element program in order to perform static and dynamic analysis for IBS structure equipped with proposed wall to wall connection.Beside the physical model and analytical model of the proposed connection,development of this connection has also been performed through finite element simulation in all degree of freedoms include of translations and rotations. Accordingly, the developed finite element model for the precast wall equipped with proposed connection is subjected to progressive monotonic, cyclic and earthquake loads to evaluate the performance of the proposed connection under static and dynamic excitation and compare with the conventional IBS wall connection in terms of capacity, energy dissipation,stress,deformation, and concrete damages in plastic range.In general, the results indicated that the capacity and energy dissipation of proposed precast wall connection subjected to monotonic and cyclic load respectively is more than that in the counterpart in all six degree of freedoms (DOFs). Dynamic responses of aforementioned connections show that using proposed wall-wall connection can effectively diminish earthquake effects in buildings and reduce seismic responses. It is concluded that the proposed wall to wall connection can be used successfully in IBS structures subjected to static and dynamic load and able to successfully dissipate vibration effect on IBS structure.